2010
DOI: 10.1021/ol102628x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Selectivity in Gold-Catalyzed Cyclizations of 3,3-Disubstituted 1,4-Diynes

Abstract: A general synthetic access to 3,3-disubstituted 1,4-diynes bearing a quaternary carbon center from acetylacetone was developed. The compounds were cyclized to the corresponding enol ethers by cationic gold complexes. The reactions occur in complete exo-selectivity in contrast to compounds incorporating an alkoxy substituent in the 3-position. A mechanistic rationale for this reversal of selectivity is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The preparation of 5a was achieved by benzylation of 7 with 1a . When the reaction was performed under the conditions reported by Czekelius et al., 5a was obtained in 86% 17a. The yield of 5a amounted to 89 % when the protocol of Gooden et al.…”
Section: Resultsmentioning
confidence: 87%
“…The preparation of 5a was achieved by benzylation of 7 with 1a . When the reaction was performed under the conditions reported by Czekelius et al., 5a was obtained in 86% 17a. The yield of 5a amounted to 89 % when the protocol of Gooden et al.…”
Section: Resultsmentioning
confidence: 87%
“…Similar reaction, by utilizing sterically overcrowded monodentate gold‐carbene complex also revealed endo ‐regiochemistry albeit with low enantioselectivity [327] . The same group observed a reversal of regioselectivity from endo to exo in the cyclization of 3,3‐disubstituted‐1,4‐diynes 229 leading to structures bearing all carbon quaternary centers 230 (Scheme 47, eq 2) [328] . Enantioselective desymmetrization of 1,4‐diynamides 231 leading to enantiopure pyrrolidines 232 are also accessible through this methodology by employing gold(I)‐binol phosphate complex (Scheme 47, eq 3) [329] .…”
Section: Cyclization Of Nitrogen‐centred Nucleophiles Towards C−c Multiple Bondsmentioning
confidence: 87%
“…Control experiments showed that the different inductive effects of alkoxy substituents do not sufficiently explain this reversal in regioselectivity, since the oxygen atom needs to be incorporated in the substituent carrying the nucleophile in order to steer the reaction towards endo ‐cyclization . In order to account for these observations, a stereoelectronic effect has been proposed (Scheme ).…”
Section: Discussionmentioning
confidence: 99%